"The most ridiculous virus in the history": The role of devaluation in COVID-19 vaccine hesitancy - Barzut Vesna; Knežević Jasmina; Blanuša Jelena (TIMS: Acta, 2021)
A cross-sectional study was conducted during the first wave of the COVID-19 pandemic (March and April 2020) in the Republic of Serbia, with the aim to evaluate the relationship between coping strategies and readiness to get a vaccine against coronavirus. At that time vaccines against COVID-19 were not developed. Coping strategies were measured on the Cybernetic Coping scale. Results confirmed that coping strategies could predict someone's negative attitudes toward vaccination. Namely, more frequent usage of devaluation was negatively associated with someone's intention to get vaccinated. It seems that underestimating the danger, believing that pandemic is not real, that COVID-19 is "just another flu-like virus" reasonably decreases the chance that someone will take precautionary measures.